2006
DOI: 10.1098/rstb.2005.1775
|View full text |Cite
|
Sign up to set email alerts
|

Adventures in vascular biology: a tale of two mediators

Abstract: I would like to thank the Royal Society for inviting me to deliver the Croonian Lecture. In so doing, the Society is adding my name to a list of very distinguished scientists who, since 1738, have preceded me in this task. This is, indeed, a great honour. For most of my research career my main interest has been the understanding of the normal functioning of the blood vessel wall and the way this is affected in pathology. During this time, our knowledge of these subjects has grown to such an extent th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
66
0
3

Year Published

2007
2007
2019
2019

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 100 publications
(69 citation statements)
references
References 233 publications
(288 reference statements)
0
66
0
3
Order By: Relevance
“…Previous studies indicate that PG effects on endothelial permeability and vascular tone may be mediated in part by cAMP-dependent protein kinase [4,46]. However, PKA-independent signaling pathways activated by PGI 2 are much less investigated.…”
Section: Involvement Of Camp and Pka In Pg-induced Rac Activation Andmentioning
confidence: 99%
“…Previous studies indicate that PG effects on endothelial permeability and vascular tone may be mediated in part by cAMP-dependent protein kinase [4,46]. However, PKA-independent signaling pathways activated by PGI 2 are much less investigated.…”
Section: Involvement Of Camp and Pka In Pg-induced Rac Activation Andmentioning
confidence: 99%
“…Since 1980, when Furchgott & Zawadzki (51) first reported that the vasodilation response to ACh requires the presence of an intact endothelium, the role of the endothelium in the regulation of vascular tone has attracted considerable interest (see 54). Action on endothelial receptors by a number of vasoactive substances stimulates the production of endothelium-derived relaxing factors (EDRF), endothelium-derived hyperpolarizing factor, and endothelium-derived constricting factors (EDCF) (see 50).…”
Section: Endotheliummentioning
confidence: 99%
“…When there is sufficient oxygen, the enzyme predominates in its oxidized state while, as the oxygen decreases and becomes limiting, the enzyme is more abundant in its reduced state. The discovery that nitric oxide (NO, a gas that closely resembles oxygen structurally) is an endogenous mediator, 6 together with the later demonstration in in vitro experiments of the interaction between NO and oxygen at the CcO and the fact that this enzyme has a greater affinity for NO than for oxygen [7][8][9] suggested that this interaction might be physiologically relevant. In spite of some controversy 10 there is increasing evidence to suggest that NO and oxygen do interact physiologically at the level of the CcO.…”
mentioning
confidence: 99%